Thermal Conductivity and Mechanical Characterization of Bamboo Fiber and Rice Husk/MWCNT Filler Epoxy Hybrid Composite. (5th September 2022) - Ramu, S.; Senthilkumar, N.; Rajendran, Saravanan; Deepanraj, B.; Paramasivam, Prabhu
Abstract : Recent trends utilizing recycled materials from around the world aim to improve a wide range of industrial and domestic applications. The natural fiber/filler matrix is used to evaluate the mechanical qualities of the hybrid nanocomposites. The specific concentration is dealing with a bidirectional bamboo fiber mat/rice husk particle/MWCNT blend with epoxy composite. The experimental work plan to execute with the three different proportional composites was as follows: bamboo fiber mat constant loading for all the specimens, but the filler particle ratio will be varied, prominently rice husk particle concentrated for all the three specimens: 5%, 10%, and 15%, and additionally, MWCNT drawn two specific specimens (2 and 3): 0.5% and 1% based on the fiber/filler concentration balanced the epoxy resin. The research presented here is hybrid nanocomposite experimented with thermal, mechanical, and morphological characterization. Thermal conductivity measured by Lee's disc method is observed at 0.2577 W/mK for specimen 3. The tensile and flexural properties are higher for 0.5% MWCNT concentration (specimen 2): 42.66 MPa and 54.72 MPa, respectively. The maximum impact strength is reached at 1% MWCNT concentration (specimen 3). Bamboo fiber and rice husk filler matrix composite (specimen 1) reached extremities shore-D hardness 84. Scanning electron microscopy was performed to examine the morphological characteristics of the tensile fractography specimen and analyzed the dispersion of the fiber/filler matrix adhesion of the surface. The bamboo fiber mat/rice husk/MWCNT (specimen 3) filler had better binding and observed fewer fiber pull-out, fiber fracture, fiber extension, and voids. In the graphic comparison, 0.5% MWCNT achieved more mechanical properties than the other two combinations.